Art for science communication: The transformation in the personal sphere of adolescents in response to climate change - Truong Thi Kim, Oanh (Curtin University, 2023)
At the core of the study, it aims to make an in-depth and critical interpretation based on the data analysis through codes. The codes vary in the length of the text to highly conceptual answers (given by four groups: control and experimental groups). The study advocates that proper science communication through art-informed collaboration should be considered to achieve sustainability outcomes. The findings are expected to develop and show how arts can influence and effectively communicate with young people as the future generation through creative and attractive narratives with proper knowledge of climate change adaptation. The study results may have implications for climate change policymakers.